Comparing coronal discoloration between AH26 and ZOE sealers - maryam zare jahromi; Amir Arsalan Navabi; Mahsa Ekhtiari (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2011)
INTRODUCTION: Intrinsic tooth discolorations after endodontic treatment are principally attributed to the composition of necrotic pulp tissue, hemorrhage within the pulp cavity, endodontic medicaments and/or filling materials. Residual sealer left in pulp chamber after obturation can cause discoloration. The objective of this in vitro study was to evaluate coronal discoloration created by AH26 and ZOE sealers after four months. MATERIALS & METHODS: Fifty intact human extracted maxillary central incisors were employed. Access cavities were prepared in all samples and root canals were instrumented; coronal orifices were then sealed using self-cure glass ionomer. The teeth were divided into two experimental groups (n=20) according to utilized sealer in pulp chambers including AH26 and Dorifill (ZOE). The remaining 10 teeth served as negative and positive controls (n=5). The access cavities were sealed with self-cure glass ionomer. Teeth were kept in incubator for four month. Preliminary digital images of the teeth were taken and then compared with those related to 4-month follow-up. The images were assessed using Photoshop software. Data was analyzed using paired t-test and independent samples t-test. RESULTS: The teeth which were filled with AH26 sealer showed significantly greater discoloration than those filled with ZOE sealer (Dorifill) (P < 0.05). CONCLUSION: AH26 sealer causes greater discoloration of the crown compared to ZOE sealer. Despite the other disadvantage of AH26 sealer, it seems that Dorifill is more esthetically considerate.